تحليل اقتصادي للعوامل المؤثرة في يمو أسعار أسهم الشركات الصناعية المساهمة في العراق للمدة (1992-2004* ) (المجلة العراقية للعلوم الاقتصادية, 2018)
The aim of this study was to evaluate the relationship between the independent variables (rate of returns on capital) and the share prices of industrial companies .The results showed that the rate of annual closing price was (0.4%) . On other hand the results also showed that the rate of growth of returns on owned and total capital and the value of each share from distributed profits were negative which is not consistent with economic logic . The results of all functions used in the analysis that the signs of most coefficients and their values were not consistent with economic logic, in spit of their significances on the level of the model as a whole. In addition the value of () was (56%) which means that there are other factors such as speculation and the absence of financial declaring and market makers in addition to different tricks practiced in such markets . The research included some conclusions and suggestions that could be found at the end of the research